Education on Health Protocols during the COVID-19 Pandemic to the Community of Cilawu Village, Garut Regency - Rd. Aldizal Mahendra Rizkio; Arfina Septiansyah; Idris Sobar Toharudin; Lukman Nul Hakim; Resti Putri Septiani Dewi (Indonesian Journal of Community Empowerment (IJCE), 2022)
ABSTRACT The low level of public awareness in breaking the chain of Covid-19 spread in Cilawu Village is of particular concern in the community service program organized by the Garut University Student Community Service group. There are three methods used, namely, educational methods, socialization methods, and program evaluation. Based on the problem analysis, the service program focuses on the following: 1) making posters for the prevention of Covid-19, 2) health education, 3) distribution of Personal Protective Equipment (PPE), 4) strengthening Village groups with brief education The impact of this service program shows that, to increase public awareness of the prevention of Covid-19 will not run optimally if there is no direct approach to the community by the local government and village government. The results of a survey evaluation regarding public awareness of the prevention of Covid-19 in Cilawu Village showed a poor response to the aspects of using masks, washing hands and using a hand sanitizer. Of the 20 respondents we observed that only 30 percent of the people of Cilawu Village realized that they often wash their hands and use them. handsanitaizer, and the remaining 70 percent said it was still occasional. This data shows that the awareness of the people of Cilawu Village about the habit of maintaining regular hand hygiene is still lacking. But on the other hand, as many as 70 percent of the people of Cilawu Village are aware of using masks if they want to travel, the remaining 30 percent stated that it is still occasional, this is of course a positive value that people obey Government policy to always use masks, but the percentage decreases for their condition. who are sick, only 50 percent of the people use masks. This needs to be of particular concern for local governments to continue to socialize their citizens regarding the use of masks. ABSTRAK Rendahnya kesadaran masyarakat dalam memutus rantai penyebaran Covid-19 di Desa Cilawu menjadi perhatian khusus dalam program pengabdian masyarakat yang diselenggarakan oleh kelompok KKN Mahasiswa Universitas Garut. Metode yang digunakan ada tiga yaitu, metode edukasi, metode sosialisasi, dan evaluasi program. Berdasarkan analisis masalah maka program pengabdian fokus pada hal berikut : 1) pembuatan poster pencegahan Covid-19, 2) penyuluhan kesehatan, 3) pembagian Alat Pelindung Diri (APD), 4) penguatan kelompok Desa dengan edukasi singkat Dampak program pengabdian ini menunjukkan bahwa, untuk meningkatkan kesadaran masyarakat terhadap pencegahan Covid-19 tidak akan berjalan optimal jika tidak dilakukan pendekatan langsung kepada masyarakat oleh Pemerintah daerah dan Pemerintah Desa. Hasil evaluasi survei mengenai kesadaran masyarakat terhadap pencegahan Covid-19 di Desa Cilawu menunjukkan respon yang kurang baik pada aspek penggunaan masker, mencuci tangan dan menggunakan handsanitaizer.Dari 20 respondense yang kami amatai hanya 30 persen masyarakat Desa Cilawu yang menyadari untuk sering mencuci tangan dan menggunakan handsanitaizer, dan sisanya sebanyak 70 persen menyatakan masih kadang-kadang. Data ini menunjukkan bahwa, kesadaran masyarakat Desa Cilawu akan kebiasaan menjaga kebersihan tangan dengan rutin masih kurang. Namun disisi lain sebanyak 70 persen masyarakat Desa Cilawu sudah menyadari untuk menggunakan masker jika ingin bepergian, sisanya sebanyak 30 persen menyatakan masih kadang-kadang, hal ini tentunya menjadi nilai positif bahwa masyarakat mentaati kebijakan Pemerintah untuk selalu menggunakan masker, namun persentase menurun untuk kondisi mereka yang sakit, hanya 50 persen masyarakat menggunakan masker. Hal ini perlu menjadi perhatian khusus bagi Pemerintah daerah untuk mensosialisasikan terus kepada warganya terkait penggunaan masker.